Redesign of a fixture mount to be used as an impression coping and a provisional abutment as well - Glenn Hsuan-Chen Chang; Chen Tian; Yuen-Siang Hung (Wolters Kluwer Medknow Publications, 2011)
Purpose: An integrated fixture mount/impression coping/ temporary abutment can provide many advantages for immediate loading of dental implants, such as simpler procedure, less chair time, cost reduction, and comfort for the patients. Materials and Methods: A newly designed dental implant fixture mount (DIFMA) can be used as an impression coping for taking an immediate impression. An immediate load provisional prosthesis can then be fabricated shortly after implant placement to immediately load the implants. This fixture mount can also serve as a temporary abutment for immediate chair-side fabrication of provisional prosthesis. Two clinical cases are presented. Results: A clinical case utilizing the fixture mount abutment (DIFMA)/implant assembly is presented. The precision of fitting between the impression copings and implants is secured with this system. The chair time for taking an immediate impression is greatly reduced. Less cost for the restoration is provided and patient comfort is delivered. Conclusions: More patient satisfaction can be conferred by employing the fixture mount in the process of immediate impression taking and as an immediate provisional abutment.